Implementation of Remote Steering System on RC Boat Trash Collector Based on Solar Energy - Entikaria Rachmanita, Risse; Kasful Nghoman Aditya, Moch. Roghib; Hasbiyati, Haning; Nur Karimah, Cahyaning; Anwar, Saiful; Rudiyanto, Bayu (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Trash, especially plastic trash in the water, remains a problem in Indonesia due to the fact that conventional methods are restricted and employ inefficient heavy equipment. Automation-based technological solutions, such as the Remote Controlled (RC) Boat Trash Collector, are promising and sustainable answers. This research focuses on the design and implementation of a remote steering mechanism for a solar-powered RC Boat Trash Collector. This system is energized by solar panels as a source of renewable energy, a conveyor system for garbage picking, and a Jumper T-Lite V2 2.4 GHz frequency remote control as the main controller. The process of research was carried out by designing, constructing, and testing the performance of the ship, for example, testing the drive motor, servo rudder, conveyor system, and test range control. The test results showed that the steering system responds well with an effective range of up to 300 meters, and the solar panels can extend the vessel's operating time. The conveyor mechanism also performs well in gathering floating debris into a collection bin. By the integration of this system, the RC Boat Trash Collector has proven to be effective, efficient, and environmentally friendly in assisting waste cleaning in bodies of water while being a platform for the implementation of sustainable, renewable energy technology.